New Challenges in Residual Stress Measurements and Evaluation 2020
DOI: 10.5772/intechopen.90409
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Evaluation with Contour Method for Thick Butt Welded Joint

Abstract: Thick plate with high tensile strength steel is increasingly employed for offshore structure fabrication, and welding residual stress is essential for assessment of mechanical performance and fatigue toughness. Therefore, it has been becoming the research issue to evaluate the distribution and magnitude of welding residual stress during butt welding of thick plate. With its advantages, contour method (CM) can be used for longitudinal residual stress evaluation by means of measuring sectional shrinkage after cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Measurement techniques used within the proposed database include a combination of DHD, ND and CM (discussed in greater detail in other reports [16,17]).
Figure 3 Experimental through-thickness residual stress profiles gathered from literature illustrating comparison between austenitic and ferritic pipe girth weld measurements using a combination of DHD, ND and CM with BS 7910 low heat input upper bound [12,2734].
…”
Section: Database Of Transverse Residual Stress Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement techniques used within the proposed database include a combination of DHD, ND and CM (discussed in greater detail in other reports [16,17]).
Figure 3 Experimental through-thickness residual stress profiles gathered from literature illustrating comparison between austenitic and ferritic pipe girth weld measurements using a combination of DHD, ND and CM with BS 7910 low heat input upper bound [12,2734].
…”
Section: Database Of Transverse Residual Stress Measurementsmentioning
confidence: 99%
“…Statistical analysis of pipe girth welds has been carried out in previous studies [1012] by combining the results of different pipes. This method involves normalising the measurement position relative to the internal surface of the pipe ( z ) by the section thickness ( B ) and the magnitude of residual stress by the material yield strength .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the contour method premises on macroscopic mechanical relaxation, it is, therefore, indifferent to material features on the atomic level. Zhang et al [17] showed that the contour method is very suitable for evaluating residual stresses in welds at high thicknesses.…”
Section: Introductionmentioning
confidence: 99%